Genomic Insights Into the Mycobacterium kansasii Complex: An Update - Jagielski, Tomasz; Borówka, Paulina; Bakuła, Zofia; Lach, Jakub; Marciniak, Błażej; Brzostek, Anna; Dziadek, Jarosław; Dziurzyński, Mikołaj; Pennings, Lian; van Ingen, Jakko; Žolnir-Dovč, Manca; Strapagiel, Dominik (Frontiers in Microbiology, 2020)
Only very recently, has it been proposed that the hitherto existing Mycobacterium kansasii subtypes (I-VI) should be elevated, each, to a species rank. Consequently, the former M. kansasii subtypes have been denominated as Mycobacterium kansasii (former type I), Mycobacterium persicum (II), Mycobacterium pseudokansasii (III), Mycobacterium innocens, (V), and Mycobacterium attenuatum (VI). The present work extends the recently published findings by using a three-pronged computational strategy, based on the alignment fraction-average nucleotide identity, genome-to-genome distance, and core-genome phylogeny, yet essentially independent and much larger sample, and thus delivers a more refined and complete picture of the M. kansasii complex. Furthermore, five canonical taxonomic markers were used, i.e. 16S rRNA, hsp65, rpoB, and tuf genes, as well as the 16S-23S rRNA intergenic spacer region (ITS). The three major methods produced highly concordant results, corroborating the view that each M. kansasii subtype does represent a distinct species. This work not only consolidates the position of five of the currently erected species, but also provides a description of the sixth one, i.e. Mycobacterium ostraviense sp. nov. to replace the former subtype IV. By showing a close genetic relatedness, a monophyletic origin, and overlapping phenotypes, our findings support the recognition of the M. kansasii complex (MKC), accommodating all M. kansasii-derived species and Mycobacterium gastri. None of the most commonly used taxonomic markers was shown to accurately distinguish all the MKC species. Likewise, no species-specific phenotypic characteristics were found allowing for species differentiation within the complex, except the non-photochromogenicity of M. gastri. To distinguish, most reliably, between the MKC species, and between M. kansasii and M. persicum in particular, whole-genome-based approaches should be applied. In the absence of clear differences in the distribution of the virulence-associated region of difference 1 genes among the M. kansasii-derived species, the pathogenic potential of each of these species can only be speculatively assessed based on their prevalence among the clinically relevant population. Large-scale molecular epidemiological studies are needed to provide a better understanding of the clinical significance and pathobiology of the MKC species.